Empowerment in Chinese primary caregivers of post-stroke patients with disability: A cross-sectional study. Issue 5 (5th February 2021) - Liu, Youhua; Guo, Hong
Abstract : Abstract: To investigate the status quo of empowerment ability of primary caregivers in post-stroke patients with disability and its influencing factors. A cross-sectional design and a convenience sample were used. Participants (N = 189) from 3 hospital in Beijing were recruited from October 2018 to June 2019. The following measurement tools were used in this study: Barthel index, Main Caregiver Empowerment Measurement, General Self-Efficacy Scale, Simplified Coping Style Questionnaire and Social Support Rating Scale. Multiple linear stepwise regression analysis was used to statistically infer the influencing factors of empowerment ability of primary caregivers. The total score of main caregivers' empowerment measurement among the participants was 161.03 ± 14.678, the median (interquartile range) score was 162.00 (150.00–171.50). The average scores of each dimension ranged from high to low: relationship with the person being cared for, goodwill care, expectation for care outcomes, subjectivity of caregiver, faith in care, understanding of care role, knowledge and skills of care, scruples about the surroundings, personal resources. The single factor analysis showed that the patient's payment method for medical expenses, whether the patient accompanied by other chronic diseases and the gender of the caregiver had an effect on the empowerment ability of primary caregivers, and the positive coping style, negative coping style, self-efficacy and subjective support of primary caregivers were positively correlated with their empowerment ability ( P < .05). Multiple linear stepwise regression analysis showed that the type of payment for treatment of patients ( b = 7.449, P < .01), and gender of caregivers ( b = 5.039, P < .05), subjective support of caregivers ( b = 0.439, P < .05), positive coping style of caregivers ( b = 0.585, P < .01), self-efficacy of caregivers ( b = 6.456, P < .01) were the main influencing factors of empowerment ability of primary caregivers. The empowerment ability of the primary caregivers of post-stroke patients with disability in China is at the upper middle level. However, there are more scruples about the surrounding and less personal resources, which deserve attention. Furthermore, the identification of the factors related to empowerment lays a foundation for clinical nursing practitioners to further develop targeted interventions on empowerment of caregivers.